Under the hawthorn tree - Conlon-McKenna, Marita; Teskey, Donald (Dublin : O'Brien Press, 1990)
During the Great Famine in Ireland in the 1840s, three children are left alone and in danger of being sent to the workhouse, so they set out to find the great-aunts they remember from their mother's stories.
5.1
5-8
Keywords: Brothers and sisters -- Fiction; Famines -- Ireland -- Fiction; Historical fiction; Famines -- Ireland -- Fiction; Historical fiction; Siblings -- Fiction; Ireland -- History -- 1837-1901 -- Fiction; Ireland -- History -- Fiction